Pengaruh Beban Kerja Dan Gaya Kepemimpinan Transformasional terhadap Kepuasan Kerja Dan Kinerja Perawat (Studi pada RSIA Puri Bunda Malang) - Errina Soufi Widiasari; N. Rachma; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2020)
Abstract This study aims to determine the Effect of Workload and Transformational Leadership Style on Job Satisfaction and Performance (Study at RSIA Puri Bunda Malang). In this study there are independent variables, namely workload and transformational leadership style, the dependent variable is performance, and the mediating variable, namely job satisfaction. Data collection methods used were questionnaires and documentation. Methods of data analysis using path analysis, direct influence test and single test The results of this study are: (1) Workload Variables have a direct significant effect on the value of Job Satisfaction, (2) Transformational Leadership Style have a direct significant effect on the value of Job Satisfaction, (3) Workload Variables do not have a significant direct effect on performance, (4) Transformational Leadership Style has a significant direct effect on performance, (5) Job satisfaction variables have a direct significant effect on performance, (6) Workload Variables has an indirect effect on performance mediated with job satisfaction, (7) Transformational Leadership Style has an indirect effect on performance mediated with job satisfaction. Keywords: Workload, transformational leadership style, Job Satisfaction, and Performance.